THE DEVELOPMENT OF AN ANDROID-BASED ETHNOMATHEMATICS PUZZLE GAME MEDIA ON FLAT-BUILT GEOMETRY MATERIAL - Hidayatulloh, Hidayatulloh; Sapri, Johanes; Susanta, Agus; Danim, Sudarwan; Winarni, Endang Widi (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
The use of ethnomathematics puzzle games as a means of educational mathematics learning that is implemented in learning not only conveys material, but can also raise potential and culture. One of the materials implemented in the ethnomathematics puzzle game is flat geometric shapes. This research aims to develop learning media for an Android-based ethnomathematics puzzle game on flat geometric material. The method used is research and development with a 4-D development model. This research was conducted at a public junior high school in Pesawaran Regency, Lampung with a total of 183 subjects. Data collection techniques use observation, interviews and tests. Data analysis used in this research uses descriptive analysis. Based on the data analysis carried out, the average product validation score for media experts was 81.0 and material experts 81.0 in the valid category. The product developed is also relatively practical, the average score of 44.5 is in the very good category. The product developed was measured using posttest and pretest scores in the experimental class and control class with an average score of 58.92 for the experimental class and 9.40 for the control class based on N-Gain Score analysis, so the ethnomathematics puzzle game is quite effective for learning.